Challenges Facing the Use of Multimedia in Teaching and Learning in Secondary Schools in Muhanga District, Rwanda - Faustin Iyamuremye; Dr. Jean Baptiste Ndagijimana (International Journal on Integrated Education, 2022)
Research has confirmed several benefits of using multimedia in teaching and learning including increased students’ interest in the lesson, and widening students’ knowledge and understanding. Multimedia teaching is credited to create a context for subject teaching as it stresses the role of students and enhances the importance of “interaction” between teachers and students. In addition, also promotes the capacity of students to communicate, trains and improves their ability to listen and speak, and to develop the communicative competence, a process during which, the teacher’s important role becomes that of a facilitator. In addition, using multimedia in teaching is also flexible; and the context can be created not only in the classroom but also after class. In a bid to improve the quality of education, the Government of Rwanda introduced the Competence-based curriculum in 2015; and rolled out a series of reforms to ensure the use of ICT and multimedia in teaching and learning in the country. Key initiatives for the high school education system included the creating smart classrooms in 2016, as well as the one-laptop per teacher program kicked-off in 2021. However, proper implementation relies on several factors such as availability and access to ICT and multimedia resources for teachers and students, as well as their expertise in using such tools. This study evaluates the challenges facing the use of multimedia in teaching and learning in Muhanga District, Rwanda; and draws pertinent recommendations to improve the quality of education through the use of multimedia in teaching and learning in Rwanda.